A primer of host-plant specialization in bees. Issue 1 (10th March 2020) - Rasmussen, Claus; Engel, Michael S.; Vereecken, Nicolas J.
Abstract : The bee-flower biological association is one of the most famous examples of insect-plant interactions, and it is axiomatic that these are of critical importance for sustaining thriving terrestrial ecosystems. Yet, the most familiar associations are often artificially managed agricultural ecosystems, reflecting an exceptionally narrow range of bee species (often only one) and a concomitantly restricted range of associated behaviors, morphologies, and mechanisms tied to pollination. Here we provide a brief account of the range of bee-floral associations encompassing floral specialization in terms of diet, behavior, and morphology. These natural associations not only promote healthy ecosystems, but also can be integrated in sustainable ways for more efficient pollination of crops by targeting bee species whose diets, behaviors, and pollen-gathering structures evolved precisely to visit such floral species rather than less efficient, and often non-native, generalists that are otherwise exploited for such purposes.